Analysis of Omission and Addition Errors Found in the Students’ English Texts - Harisna Hikmah (Journal of English Language Teaching and English Linguistics, 2020)
The research was done to find the aspects of omission and addition errors in English texts made by the students of MAN 3 Bantul. The research was a descriptive study which was conducted in MAN 3 Bantul. The data was collected by analyzing the students’ writing. There were 20 exposition texts made by the eleventh-grade students of MAN 3 Bantul. The text is written in four different themes. After getting the data, the data were analyzed by identifying and deeply checking the students’ errors according to the theory form James (1998). The data found then categorized by entering the data to the table based on the linguistic taxonomy and surface strategy taxonomy. There were many aspects of omission or addition errors found in this study. From the data analysis, the study found seven aspects of omission errors and six aspects of addition errors. The aspects of omission errors were omission of (1) to be, (2) article, (3) pluralization, (4) verb, (5) preposition, (6) pronoun, and (7) agreement. While the aspects of addition errors were addition of (1) preposition, (2) article, (3) conjunction, (4) to be, (5) sub clause marker, and (6) verb. It can be concluded that the students still have lack of grammatical mastery and implies that grammar should be inserted in the teaching and learning process. It implies that the students should be given enough opportunity in learning English grammar more. The teacher should also increase their awareness concerning with the errors made by the students. They have to give more emphasize and also feedback to increase the students’ awareness in applying English grammar rule in creating sentence or texts.